ANALISIS KEBUTUHAN PENGEMBANGAN SDM BIDANG BINA MARGA DINAS PUPR PROVINSI NTB - Dewi Utary; Agusdin Agusdin; Hermanto Hermanto (Master of Management, Mataram University, 2018)
This study aims to analyze the workload of each work unit and the category of human resources (HR), analyze the number and HR competencies of each work unit and to analyze the types of human resource development needed by the Highways Department of the Public Works and Spatial Planning ( PUPR) West Nusa Tenggara Province (NTB). The population in this study were all employees who worked on the Highways Sector of the PUPR Provincial Office of NTB Province which numbered 49 people. The population in this study were all employees working in the Highways Division of the Public Works Department of West Nusa Tenggara Province with documentation techniques, questionnaires, in-depth interviews and Focus Group Discussion (FGD) as the data collection methods used. The data analysis technique used in this study is WISN (Workload Indicators of Staffing Need). The results showed that the workload for each unit in the Highways Sector of the PUPR Office of NTB Province was still not optimal, there were a shortage of human resources of 34 people consisting of 24 (twenty four) technical personnel and 10 (ten) non-technical personnel, as well as still need HR development to improve HR competencies. Penelitian ini bertujuan untuk menganalisis beban kerja masing-masing unit kerja dan kategori sumber daya manusia (SDM), menganalisis kebutuhan jumlah dan kompetensi SDM masing-masing unit kerja dan untuk menganalisis jenis pengembangan SDM yang dibutuhkan Bidang Bina Marga Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Provinsi Nusa Tenggara Barat (NTB). Populasi pada penelitian iniadalah seluruh karyawan yang bekerja pada Bidang Bina Marga Dinas PUPR Provinsi NTB yang berjumlah 49 orang. Populasi dalam penelitian ini adalah seluruh karyawan yang bekerja pada Bidang Bina Marga Dinas PUPR Provinsi NTB dengan teknik dokumentasi, angket, wawancara mendalam (Indepth Interview), dan Focus Group Discussion (FGD) sebagai metode pengumpulan data yang di gunakan.Teknik analisis data yang digunakan dalam penelitian ini adalah WISN (Workload Indicators of Staffing Need). Hasil penelitian menunjukkan bahwa beban kerja pada setiap unit pada Bidang Bina Marga Dinas PUPR Provinsi NTB masih belum optimal, terdapat kekurangan SDM sejumlah 34 orang yang terdiri dari 24 orang tenaga teknis dan 10 orang tenaga non teknis, serta masih membutuhkan pengembangan SDM untuk peningkatan kompetensi SDM.Keywords:Workload, Human Resource Needs, Workload Indicators of Staffing Need (WISN), Needs Assesement. Beban Kerja, Kebutuhan Sumber Daya Manusia, Workload Indicators of Staffing Need. (WISN), Needs Assesement.